2012
DOI: 10.1016/j.cub.2012.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide Reductase Activity Is Coupled to DNA Synthesis via Proliferating Cell Nuclear Antigen

Abstract: Summary Synthesis of dNTPs is required for both DNA replication and DNA repair and is catalyzed by ribonucleotide reductases (RNR), which convert ribonucleotides to their deoxy forms [1, 2]. Maintaining the correct levels of dNTPs for DNA synthesis is important for minimising the mutation rate [3-7], and this is achieved by tight regulation of ribonucleotide reductase [2, 8, 9]. In fission yeast, ribonucleotide reductase is regulated in part by a small protein inhibitor, Spd1, which is degraded in S phase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…-dependent ubiquitylation and subsequent degradation of Spd1 (Salguero et al, 2012). This motif is present in Spd2 (Fig.…”
Section: Cdt2mentioning
confidence: 96%
See 1 more Smart Citation
“…-dependent ubiquitylation and subsequent degradation of Spd1 (Salguero et al, 2012). This motif is present in Spd2 (Fig.…”
Section: Cdt2mentioning
confidence: 96%
“…-mediated ubiquitylation Liu et al, 2003), a process that occurs on chromatin-associated PCNA (Salguero et al, 2012). Spd1 degradation also requires the Csn1 and Csn2 subunits of the COP9 signalosome (Liu et al, 2003).…”
Section: Cdt2mentioning
confidence: 99%
“…Cdt2 (Salguero et al, 2012). Thus, lack of CRL4 Cdt2 might lead to replication stress by Spd1 interfering with PCNA-controlled fork fidelity in addition to its effect on RNR.…”
Section: Spd1 Targets Functions Other Than Ribonucleotide Reductionmentioning
confidence: 99%
“…Spd1 is targeted for degradation through ubiquitylation mediated by the CRL4 Cdt2 ubiquitin ligase as cells enter S phase or experience DNA damage (Liu et al, 2003;Bondar et al, 2004;Holmberg et al, 2005). In both cases, Spd1 is recruited to Cul4-Ddb1 through MBFmediated transcriptional induction of the adaptor Cdt2 and association with DNA-bound PCNA (Salguero et al, 2012). Mutants of the CRL4 Cdt2 ubiquitin ligase fail to degrade Spd1 in response to S phase entry and DNA damage, with the major consequences of increased mutation rates and damage sensitivity in addition to checkpoint activation and dependency.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (13) proposed that destruction converts DNA polymerase ␦ to a three-subunit enzyme, which is less error-prone, whereas Terai et al (14) suggested that destruction is necessary for fork stalling following DNA damage. Other substrates of CRL4 Cdt2 include the transcription factor E2f1 in flies (15) (to turn off the G 1 expression program in S phase), the ribonucleotide reductase inhibitor Spd1 in fission yeast (16,17) (to up-regulate dNTP synthesis in S phase and after DNA damage), and the translesion DNA polymerase POLH-1 in worms (18) (to avoid mutagenic translesion DNA synthesis).…”
Section: Crl4mentioning
confidence: 99%